Legal Reform in Settlement of Land and Housing Disputes in Urban Areas to Achieve Legal Certainty - Effendi, Lutfi; Sara, Rineke (International Journal of Social Service and Research, 2025)
Legal disputes related to land and housing in urban areas have become increasingly complex due to the growing demand for land and rapid urbanization. These disputes often involve issues of ownership, use, and control, which require effective mechanisms for resolution to ensure legal stability and protect community rights. The aim of this research is to explore the mechanisms for resolving legal disputes over land and housing in urban areas using a normative legal approach. This study examines relevant laws and regulations, legal doctrines, and pertinent literature to understand the concepts, principles, and regulations governing the resolution of such disputes. The research utilizes primary legal materials, including the Basic Agrarian Law, housing and residential regulations, and other laws pertaining to land and housing conflicts. In addition, secondary legal documents such as books, scientific journals, and expert opinions are incorporated to support the study. A qualitative normative analysis is employed to examine how existing regulations address land and housing disputes and to identify obstacles in their implementation. This research aims to contribute to the strengthening of regulations and policies in the land and housing sector, offering valuable insights for policymakers, academics, and legal practitioners in developing more effective solutions to the challenges of land and housing disputes in urban settings. The findings are expected to serve as a reference in improving legal frameworks and dispute resolution mechanisms in this area.